La gestión del talento humano como base para la efectividad de los procesos de producción (2020)
The human management evolution in organizations has allowed each of its processes to play an important role in the mission of companies dedicated to the production or transformation of raw materials. With this new conception, it is easy to identify sustainable competitive advantages that lie in human talent and widely support the achievement of the strategic objectives of organizations.